2015
DOI: 10.1016/j.bmc.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-methylarylnitrones derived from alkyloxybenzaldehydes and antineoplastic effect on human cancer cell lines

Abstract: New O-isoprenylated-N-methylarylnitrones derived from isomeric o, m and p-hydroxybenzaldehydes have been prepared and the antineoplastic effects on human cancer cell lines were evaluated. The O-geranylated nitrone LQB-278 (1b) and its isomers 2b and 3b inhibited the NO production, but the anti-leukemic activity was drastically dependent on nitrone isomer, with the 1b being the most effective one (IC₅₀ of 6.7 μM) on Jurkat leukemia cell, by MTT assay. In addition, 1b up-regulated p21CIP1/WAF1/Sdi1 protein expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
(18 reference statements)
0
14
0
Order By: Relevance
“…However, neuroprotection is still a choice, and oxidative stress, a suitable biological target. In this context, antioxidants such as N - t -butylphenylnitrone (PBN; Figure 1; Novelli et al, 1986) and NXY-059 (Figure 1; Dehouck et al, 2002), have attracted the interest of a number of laboratories, resulting in therapeutic candidates for cancer (Inoue et al, 2007; Floyd et al, 2008, 2010, 2011; Costa et al, 2015), neurodegenerative disorders (Floyd et al, 2000), hearing loss (Floyd et al, 2008) and stroke (Doggrell, 2006; Floyd et al, 2008). NXY-059 (Figure 1) (Kuroda et al, 1999) is a well-known free radical scavenger with good neuroprotective profile in rat models of transient and permanent focal ischemia, and stroke model in rodents, which has been launched several times in different program in advanced clinical studies, although with limited success (Macleod et al, 2008).…”
Section: Nitronesmentioning
confidence: 99%
“…However, neuroprotection is still a choice, and oxidative stress, a suitable biological target. In this context, antioxidants such as N - t -butylphenylnitrone (PBN; Figure 1; Novelli et al, 1986) and NXY-059 (Figure 1; Dehouck et al, 2002), have attracted the interest of a number of laboratories, resulting in therapeutic candidates for cancer (Inoue et al, 2007; Floyd et al, 2008, 2010, 2011; Costa et al, 2015), neurodegenerative disorders (Floyd et al, 2000), hearing loss (Floyd et al, 2008) and stroke (Doggrell, 2006; Floyd et al, 2008). NXY-059 (Figure 1) (Kuroda et al, 1999) is a well-known free radical scavenger with good neuroprotective profile in rat models of transient and permanent focal ischemia, and stroke model in rodents, which has been launched several times in different program in advanced clinical studies, although with limited success (Macleod et al, 2008).…”
Section: Nitronesmentioning
confidence: 99%
“…It is important to point out that the the beneficial effect of PBN in vivo against CD was a consequence of its free radical scavenging properties; however, recent reports have shown that the antileukemic properties of the PBN derivate, the O-geranylated nitrone (LQB-278), were not free radical related but a consequence of cell cycle regulation by the inhibition of p21 expression [19]. Therefore, the antioxidant property may not be the only mechanism of action of these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…LQB-123 was as active as or more active than α -tocopherol, shark cartilage, and fish oil, used as references [17, 18] Thereafter, O -isoprenylated- N -methylarylnitrones analogues have been synthetized and the antineoplastic effects on human cancer cell lines (Jurkat and leukemia) were demonstrated [19]. …”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR (400 MHz, MeOD) 8.41 (2H, d, J = 8.4 Hz), 8.07 (2H, d, J = 8.4 Hz), 7.93 (1H, s), 3.79 (2H, s), 1.57 (6H, s). 13 2-Methyl-2-nitropropyl acetate (15). Under stirring, 2-methyl-2-nitropropanol (5.18 g, 43.53 mmol) was dissolved in a pyridine/ Ac 2 O (1:1 v/v) mixture at 0 °C.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…However, PBN and its derivatives exhibited a better distribution within tissues and cells and have therefore been widely used in ex vivo and in vivo studies of radical production in whole animals, 7−9 and as antioxidant agents in several biological models. 10,11 Significant protection in various animal models of neurodegenerative diseases, 12 stroke, 13 cardiovascular diseases, 14 and cancer 15 the USA. 16,17 Linear nitrone synthesis is facile due to their final solid form at room temperature, making their purification simple where they can be recrystallized to afford products free of paramagnetic impurities.…”
Section: ■ Introductionmentioning
confidence: 99%